Porphyromonas gingivalis-Induced Neuroinflammation in Alzheimer’s Disease - Olsen, Ingar (Frontiers in Neuroscience, 2021)
“Chronic” periodontitis and its keystone pathogen Porphyromonas gingivalis, have repeatedly been associated with Alzheimer’s disease (AD). Pathological hallmarks in AD are brain accumulations of amyloid-beta (Aβ) and neurofibrillary tangles (NFT) consisting of aggregated and hyperphosphorylated tau. In addition, neuroinflammation induced by P. gingivalis, has increasingly been recognized as a factor in the pathogenesis of AD. The present mini review discusses possible mechanisms for the induction of neuroinflammation by P. gingivalis in AD, involving factors such as pro-inflammatory mediators, Aβ, tau, microglia, cathepsin B and protein kinase R. Inflammagens of P. gingivalis such as lipopolysaccharide and gingipains are also discussed.